2014
DOI: 10.1083/jcb.201404157
|View full text |Cite
|
Sign up to set email alerts
|

Cis-acting DNA sequence at a replication origin promotes repeat expansion to fragile X full mutation

Abstract: An SNP upstream of the CGG repeats located at a replication initiation site may contribute to origin inactivation, to altered replication fork progression through the CGG repeats, and repeat expansion to fragile X full mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 59 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…In FRDA cells, however, the majority of replication forks progress only in the 3’−5’ direction, originating from initiation sites downstream of the GAA repeats. A similar phenomenon of unidirectional fork movement through the CGG repeats at the FMR1 locus was observed in FXS hESCs (Gerhardt et al, 2014a; Gerhardt et al, 2014b). However, inactivation of a replication origin upstream of the expanded CGG repeats by a point mutation was required to elicit the alteration in replication fork direction in FXS hESCs.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In FRDA cells, however, the majority of replication forks progress only in the 3’−5’ direction, originating from initiation sites downstream of the GAA repeats. A similar phenomenon of unidirectional fork movement through the CGG repeats at the FMR1 locus was observed in FXS hESCs (Gerhardt et al, 2014a; Gerhardt et al, 2014b). However, inactivation of a replication origin upstream of the expanded CGG repeats by a point mutation was required to elicit the alteration in replication fork direction in FXS hESCs.…”
Section: Discussionsupporting
confidence: 65%
“…We examined the DNA replication program in FRDA patient cells to determine if defects in DNA replication processes cause GAA repeat expansions. We found that replication fork progression at the FXN gene is altered in FRDA cells to a much greater extent than the replication impediment we previously detected at the FMR1 locus in unaffected and FXS human embryonic stem cells (hESCs) using SMARD (Gerhardt et al, 2014a; Gerhardt et al, 2014b). The major stall detected in FRDA cells suggests that the replication fork indeed encounters a block imposed by stable non-canonical DNA structures (e.g.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Indeed, recent data on the replication patterns at the DM1 and FMR1 loci in human cells shows evidence for changes in origin usage at unstable alleles (Cleary et al ., 2010; Gerhardt et al ., 2014a; Mirkin & Mirkin, 2014). At the FMR1 locus, a common SNP identified in one of the flanking origins has been shown to be associated with an expansion-prone haplotype (Gerhardt et al ., 2014b). …”
Section: Repeat Expansions Cause Human Diseasementioning
confidence: 99%
“…The postulated “rapid path” expansion mechanism is likely more complex and could involve a cis -acting modifier of repeat length stability, a candidate for which has been identified 53 kb proximal to the repeat [36,37]. …”
Section: Factors Affecting Stability and Expansion Of The Cgg/agg mentioning
confidence: 99%